SOSIALISASI PELESTARIAN LINGKUNGAN BERBASIS KONSEP GOOD ENVIRONMENTAL GOVERNANCE DI KECAMATAN ALAM BARAJO KOTA JAMBI - Baidawi, Ahmad; Dewi, Ratna (Lembaga Pengabdian Masyarakat Universitas Swadaya Gunung Jati, 2021)
Alam Barajo District is one of the sub-districts located in Jambi City with the largest population. In terms of the environment, Alam Barajo is one of the districts that produces the largest waste in Jambi City with a waste volume of 251.36% / day according to the 2018 Jambi City Environmental Service report. In addition to the waste problem, forest destruction is also an environmental problem in Alam barajo District. The above is due to a lack of understanding and low community participation in environmental conservation in Alam Barajo District. The purpose of this activity is to provide understanding through socialization of the importance of environmental preservation properly. This Community Service activity starts from the group discussion stage, preparation, observation, and socialization of environmental conservation based on the concept of Good Environmental Governance in Alam Barajo District. Service methods are socialization, training and simulation. The delivery of socialization and training materials is carried out using several relevant methods, namely: lecture, question and answer and discussion methods. The results of the observations show that some people do not understand well how to conserve the environment. After the socialization was carried out, it was seen that the people of Alam barajo sub-district, Jambi city, were very enthusiastic with the material presented about environmental conservation based on the concept of Good Environmental, from this socialization it was hoped that the understanding, participation and awareness of the people of Jambi city in general and the people of Alam barajo sub-district in particular about environmental preservation increasing and getting better so that the achievement of Good Governance in a government.